Factors Shapping the Adoption of Mobile Marketing in Rural Areas of Tanzania: The Case of South Region in Unguja - Nuru Haji; Nasra Kara; Salum Mohammed (European Scientific Journal, ESJ, 2024)
The explosive use of mobile phones facilitates the introduction of different mobile app services which become an essential part of daily life. This forces the business vendors to place individually targeted marketing messages through mobile phones to ensure easy access to the service since the mobile phone is in the hands of owner all the day long. Most of the studies in mobile marketing adoption focused on urban and university consumers. This study aims to investigate the perception of consumers in rural areas on their intention to adopt mobile phone applications such as mobile marketing. The TAM model extended with the UTAUT2 model to achieve the study objective. a cross-sectional survey conducted to collect data through self-administered questionnaires to 500 villages owning mobile phones, through a stratified sampling design in the South district of Unguja. SEM technique was employed to analyze the collected data. The analysis was aided by SPSS version 25. The results showed that perceived usefulness, perceived ease of use, and facilitating conditions were the significant determinants of behavioral intention to adopt mobile marketing to consumers of rural areas. Furthermore, the attitude partially mediates the relationship between consumers’ perception and behavioral intention. The finding of this study is vital to business entities in the extension of mobile marketing coverage together with rural consumers to improve the way of life in the current mobile phone era. The Implications and limitations of the research were discussed.